Catalytic oxidation behavior of Sr doped cation exchange resins in Li2CO3–Na2CO3–K2CO3 system. (July 2023) - Zheng, Yang-Hai; Wang, Yue-Lin; Yan, Yong-De; Xu, Wen-Da; Xue, Yun; Liu, Xin; Ma, Fu-Qiu; Zhu, Kai
Abstract: Ion exchange resins are widely applied in radioactive liquid waste disposal. However, problems such as the volatilization of radionuclides, acid gas generation, and self-radiolysis by spent cation exchange resins (CERs) demand the development of appropriate treatment methods. Thus, in the present study, the oxidation behaviors were determined for CERs and Sr doped CERs with Li2 CO3 –Na2 CO3 –K2 CO3 by thermogravimetric analysis. Ternary alkaline molten carbonate with a low melting point was applied for the first time to treat the Sr doped CERs. This method can reduce the energy consumed disposing of CERs and neutralize the tail gases produced by the oxidation of CERs. The oxidation products were analyzed by on-site gas mass spectrometry, infrared spectroscopy, X-ray diffraction, Fourier transform infrared spectrometry, and scanning electron microscopy. After the sulfonic acid group (-SO3 H) decomposed at 300 °C, Sr species did not accelerate the oxidation of residues initially. However, they inhibited the removal of sulfur from the oxidizing residue. The carbonate salt melted at 400 °C and the molten salt effectively alleviated the volatilization of Sr and SO2, which were trapped as SrCO3 and sulfate in the molten salt. Moreover, the presence of Sr 2+ significantly enhanced the removal of sulfur from residues to 69.27% from 54.77%, and effectively increased the destruction and removal efficiency of CERs from 47.31% to 60.35% at 450 °C. These findings demonstrate that molten carbonate salt could be a suitable medium for improving the catalytic performance of Sr. Graphical abstract: Image 1 Highlights: The catalytic behavior of Sr on the oxidation process of cation exchange resins was proposed. Li2 CO3 –Na2 CO3 –K2 CO3 system was firstly applied to molten salt oxidation of Sr doped resins. Sr can effectively convert the oxidation products of SO2 and sulfone to form sulfate in the melt.